Revealing the rejuvenation mechanism of SBS modified asphalt through combined rheology-AFM-MD-DFT analysis - Zhang, Man; Zhao, Jingzhuo; Wu, Xu (Frontiers in Built Environment, 2025)
This study investigates the changes in microstructure and rheological properties of SBS modified asphalt during aging and regeneration processes. The high-temperature rutting resistance and low-temperature crack resistance at different ageing stages were characterized using a dynamic shear rheometer (DSR) and a bending beam rheometer (BBR). The effects of aging time and rejuvenator on the surface topography characteristics of asphalt were analyzed using atomic force microscopy (AFM). Molecular dynamics and density functional theory were employed to analyze the interactions between the rejuvenator and SBS modified asphalt. The results show that aging improves the resistance to high temperature deformation but reduces the temperature sensitivity, which can be effectively mitigated by rejuvenator. Aging deteriorates stress relaxation performance and low-temperature crack resistance, while rejuvenators significantly restore low-temperature properties. Aging action and rejuvenator changed the surface microstructure of SBS modified asphalt. Molecular dynamics simulations reveal that rejuvenator molecules disperse among SBS and polar molecules, reducing intermolecular forces. The density functional theory analysis indicates that the rejuvenator exhibits strong electrostatic interactions with polar molecules in aged asphalt, particularly showing significant interactions with the -COH and -COOH functional groups in the SB and BS components. These findings provide a theoretical basis for performance evaluation and optimized design of recycled asphalt.